Law's cosmos juridical discourse in Athenian forensic oratory - Wohl, Victoria, 1966-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2010)
"Recent literary-critical work in legal studies reads law as a genre of literature, noting that Western law originated as a branch of rhetoric in classical Greece and lamenting the fact that the law has lost its connection to poetic language, narrative, and imagination. But modern legal scholarship has paid little attention to the actual juridical discourse of ancient Greece. This book rectifies that neglect through an analysis of the courtroom speeches from classical Athens, texts situated precisely at the intersection between law and literature. Reading these texts for their subtle literary qualities and their sophisticated legal philosophy, it proposes that in Athens' juridical discourse literary form and legal matter are inseparable. Through its distinctive focus on the literary form of Athenian forensic oratory, Law's Cosmos aims to shed new light on its juridical thought, and thus to change the way classicists read forensic oratory and legal historians view Athenian law"--Provided by publisher.
The world of law : oratory and authority -- Legal violence and the limit of justice -- Legal fictions : subjects probable and improbable -- Logos biou : law's life stories -- Civic amnesia and legal memory : remembering and forgetting in the lawcourts -- Family/law : legal genealogies.
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Forensic oratory; Rhetoric, Ancient; Law, Greek; Law -- Greece -- Athens -- History -- To 1500.; Electronic books